The Russia scare fake news and genuine threat - Sakwa, Richard 1953- (Routledge, 2023)
"The Russia Scare assesses the scope, character and extent of Russian interference in the affairs of liberal democratic states. This book examines the 'Russia scare' in a dynamic manner, stressing the interaction between threat perception, responses and subsequent policies. What forms does this alleged meddling take, what are the instruments used, how effective are the deployed tools, and who are the allies with which Russia works in these endeavours? Above all, what impact does this work have on target societies? The book also explores why Russia engages in such activities, what the probable chain of command is (if any), and the role of the Russian leadership in all of this, as well as investigating the response of Western societies and governments. The author sifts the real from the imagined, which can only be achieved by establishing the larger historical context. He scrutinises the fundamental question: is Russia really engaged in a sustained 'hybrid warfare' campaign to sow discord and undermine Western democracies? If so, what are the strategic purposes underlying such activity? Various hypotheses are analysed, notably that Russian post-Cold War activity is nothing exceptional in the context of great power confrontation; that all great powers are engaged in one way or another in such actions, and thus contextualisation is important; and that Russia's subversive activity has been greatly exaggerated, and very often entirely misrepresented. This book will be of great interest to students, scholars and politicians of international relations, comparative politics, security and defence studies, global governance and Russian politics, as well as political advisers, NGOs, diplomats and journalists"--
Includes bibliographical references and index
Keywords: Desinformation; Information warfare; Westliche Welt; Russland; Information warfare / Russia (Federation) / History; Cyberspace operations (Military science) / Russia (Federation); Disinformation / Russia (Federation) / History; Cyberterrorism / Russia (Federation); Western countries / Foreign relations / Russia (Federation); Russia (Federation) / Foreign relations / Western countries; Russia (Federation) / Foreign relations